2014
DOI: 10.1158/1078-0432.ccr-13-2602
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aromatase Inhibition on Functional Gene Modules in Estrogen Receptor–Positive Breast Cancer and Their Relationship with Antiproliferative Response

Abstract: Purpose: To investigate potential associations between gene modules representing key biologic processes and response to aromatase inhibitors (AI) in estrogen receptor-positive (ER þ ) breast cancer.Patients and Methods: Paired gene expression and Ki67 protein expression were available from 69 postmenopausal women with ER þ early breast cancer, at baseline and 2 weeks post-anastrozole treatment, in the presurgical setting. Functional gene modules (n ¼ 26) were retrieved from published studies and their module s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 49 publications
(58 reference statements)
3
28
1
Order By: Relevance
“…For example, Miller et al [142] studied RNA expression in sequential biopsies taken before and after two weeks of neoadjuvant treatment with letrozole. The effects of 2-weeks preoperative treatment with either anastrozole or letrozole have also been examined [35,122,143]. Molecular responses detected in the studies were consistent.…”
Section: Signatures To Predict Neo-adjuvant Response To Aismentioning
confidence: 89%
See 1 more Smart Citation
“…For example, Miller et al [142] studied RNA expression in sequential biopsies taken before and after two weeks of neoadjuvant treatment with letrozole. The effects of 2-weeks preoperative treatment with either anastrozole or letrozole have also been examined [35,122,143]. Molecular responses detected in the studies were consistent.…”
Section: Signatures To Predict Neo-adjuvant Response To Aismentioning
confidence: 89%
“…In a similar study employing anastrozole pretreatment. Gao et al [143] also found that multiple processes and pathways were affected by the AI treatment. Modules closely associated with ESR1 expression were predictive of good antiproliferative response to AIs, whereas modules representing immune activity and IGF-I/MAPK were predictive of poor Ki67 response, supporting their therapeutic targeting in combination with AIs.…”
Section: Signatures To Predict Neo-adjuvant Response To Aismentioning
confidence: 98%
“…In ERC breast cancer, gene signatures that are based on proliferation often strongly correlate with Ki67 expression (Gao et al 2014), a well-known marker of proliferation. Furthermore, in ERC breast tumors in particular, it is Ki67 and not pCR that is the early correlative endpoint for predicting efficacy of both hormonal therapy or chemotherapy in ERC breast cancer (Yerushalmi et al 2010, Dowsett et al 2011, von Minckwitz et al 2012, Gao et al 2014.…”
Section: Kinase Overexpression Associated With Sensitivity To Endocrimentioning
confidence: 99%
“…Furthermore, in ERC breast tumors in particular, it is Ki67 and not pCR that is the early correlative endpoint for predicting efficacy of both hormonal therapy or chemotherapy in ERC breast cancer (Yerushalmi et al 2010, Dowsett et al 2011, von Minckwitz et al 2012, Gao et al 2014. Recently, using Yes (Wei et al 2014) neoadjuvant antiestrogen therapy (particularly AIs), it was observed that decreased detection of survival pathway activation markers (e.g.…”
Section: Kinase Overexpression Associated With Sensitivity To Endocrimentioning
confidence: 99%
“…Aromatase inhibitors (AIs) are continuously being developed that have considerable clinical impact on the production of estrogen among post-menopausal women and thereby on breast cancer [10,11] . Currently, AIs are classified into two subtypes: steroidal and non-steroidal.…”
Section: Introductionmentioning
confidence: 99%